Using Rasch Model to Analyze Reliability and Validity of Concept Mastery Test on Electricity and Magnetism Topic - Yusri Handayani; Rahmawati Rahmawati; Widiasih Widiasih (JIPF (Jurnal Ilmu Pendidikan Fisika), 2023)
This study aims to analyze the reliability and validity of the electricity and magnetismconcept mastery test (EM-CMT) using Rasch model aided by Winsteps version 3.68.2. The multiple choice concept mastery test consists of 40 items about material electric current, resistance, resistivity, Ohm's law, electric voltage, energy and electrical conductivity, resistors in series, parallel, and mixed circuits, Kirchhoff's law, RC charging and discharging capacitor circuits, magnetic fields, magnetic forces, and sources magnetic field. The sample of this study were prospective physics teacher students who had passed basic physics courses. The results showed that the EM-CMThad a value of the Alpha Cronbach reliability with a good and acceptable category (0.70). The value of person reliabilityis in the quite good category (0.69). Meanwhile, the personnel separation coefficient of 1.50 which indicates the response of respondents is quite good and consistent. Analysis of the observational aspects of item fit shows that there are no items that need to be changed or removed. For the aspect of person fit, the results of the analysis showed that there were seventeen out of sixty-three respondents who experienced unusual response patterns. A review of the observations of the map variable shows the distribution of respondents' abilities and the items are proportional. Analysis of unidimensionalaspects shows the value of "raw variance explained by measure" is in the acceptable category. Based on the results of the analysis on a number of aspects, it can be concluded that theEM-CMT test is reliable and valid so that it can be used to measure the students’ concepts.